Carriage of Gardnerella vaginalis and anaerobes in semen. - Ison, C A (1985)
Gardnerella vaginalis was isolated from 22 (38%) of 58 semen samples obtained from men attending an infertility clinic. Counts ranged from 1.2 X 10(3) to greater than 10(7) colony forming units (cfu)/ml. There was no association between the isolation of G vaginalis and the sperm count. Twenty (34.4%) samples contained non-sporing anaerobes and nine (15.5%) both anaerobes and G vaginalis. The infective dose of G vaginalis is not known, but semen could act as a medium for its sexual transmission.